Insects and other pests in Africa - Karel, A.K.; Autrique, A. (International Center for Tropical Agriculture, 1989)
One of the most important bean-production constraints in tropical and subtropical Africa is the wide range of insect pests, which attack every part of the bean plant (from roots to pods and seeds) causing heavy losses either in the field or in storage. Losses can be up to 100 percent depending on area, season, cv., planting date, and cultural practices. Ophiomyia phaseoli, which attacks seedlings, is the most important pest. The main damage is caused by larval feeding and tunneling in stem tissue. Seedlings suffer premature leaf fall and either die or become stunted. Control is done through cultural practices, the use of insecticides, and var. resistance. Liriomyza trifolii is an important pest in Egypt and Mauritius; damage is caused by the maggot which destroys leaf's palisade tissue, making serpentine tunnels. It is controlled with insecticides and the use of resistant cv. Aphis favae and Aphis craccivora are the main aphid pests affecting common beans and cowpea. Their feeding causes leaf yellowing, destruction, yield losses, and transmit and spread BCMV. Control measures include the use of insecticides and resistant cv.